2018
DOI: 10.5334/egems.198
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Leveraging “Big Data” to Advance Epidemiology and Improve Quality: Design of the VA Colonoscopy Collaborative

Abstract: Objective:To describe a framework for leveraging big data for research and quality improvement purposes and demonstrate implementation of the framework for design of the Department of Veterans Affairs (VA) Colonoscopy Collaborative.Methods:We propose that research utilizing large-scale electronic health records (EHRs) can be approached in a 4 step framework: 1) Identify data sources required to answer research question; 2) Determine whether variables are available as structured or free-text data; 3) Utilize a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Controls were veterans with no prior CRC diagnosis, normal baseline colonoscopy defined by presence of a CPT code for diagnostic colonoscopy only (45378 or G0121), and absence of a colon biopsy (as evidenced by absence of a pathology report within 30 days of baseline colonoscopy) (see online supplementary appendix table C for full outline of study selection criteria). Our prior work has shown that this approach is 96.3% sensitive and 97.5% specific for normal colonoscopy and had a positive predictive value of 97% 12 13. Additionally, to avoid inclusion of controls with missed CRC at baseline colonoscopy, controls with CRC diagnosed by VACCR or an ICD-9 code within up to 3 years of baseline colonoscopy were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Controls were veterans with no prior CRC diagnosis, normal baseline colonoscopy defined by presence of a CPT code for diagnostic colonoscopy only (45378 or G0121), and absence of a colon biopsy (as evidenced by absence of a pathology report within 30 days of baseline colonoscopy) (see online supplementary appendix table C for full outline of study selection criteria). Our prior work has shown that this approach is 96.3% sensitive and 97.5% specific for normal colonoscopy and had a positive predictive value of 97% 12 13. Additionally, to avoid inclusion of controls with missed CRC at baseline colonoscopy, controls with CRC diagnosed by VACCR or an ICD-9 code within up to 3 years of baseline colonoscopy were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Controls were Veterans with normal index colonoscopy defined by presence of a Current Procedural Terminology code for diagnostic colonoscopy only (45378 or G0121) and absence of a pathology report (within 30 days of index colonoscopy). Our previous work has shown that this definition is 96.3% sensitive and 97.5% specific for normal colonoscopy and had a positive predictive value for identifying individuals with normal colonoscopy of 97% (15,16). To avoid inclusion of controls with missed CRC at baseline colonoscopy, controls with CRC diagnosed by the VACCR or International Classification of Diseases, Ninth Revision code within up to 3 years of index colonoscopy were excluded.…”
Section: Methodsmentioning
confidence: 98%
“…To avoid inclusion of controls with missed CRC at baseline colonoscopy, controls with CRC diagnosed by the VACCR or International Classification of Diseases, Ninth Revision code within up to 3 years of index colonoscopy were excluded. If a candidate control had less than 3 years of follow-up (due to death or loss to follow-up at VA) based on the Veterans Health Administration Vital Status File, he/she was excluded (15).…”
Section: Methodsmentioning
confidence: 99%
“…Our overarching aim was to develop and validate a strategy for identifying aspirin exposure within our use case of Veterans who underwent usual care colonoscopy within the Department of Veterans Affairs (VA). The cohort was created as part of a VA Office of Research and Development-funded study to examine predictors of colorectal cancer and high-risk polyps after baseline adenoma removal 19. As exposure may impact colorectal cancer risk, we sought to identify a rigorous method for aspirin ascertainment.…”
Section: Methodsmentioning
confidence: 99%